Real-world experience of ocrelizumab in multiple sclerosis in an Arab population. Issue 1 (15th December 2021) - Garcia-Cañibano, Beatriz; Ouanes, Sami; Ganesan, Gowrii Saswathy; Yousuf, Wajiha; Humos, Basel; Baig, Tehniyat; Ibrahim, Faiza; Singh, Rajvir; Deleu, Dirk
Abstract: Objective: Pivotal clinical trials revealed good clinical efficiency of ocrelizumab while having a good safety profile in the management of multiple sclerosis (MS). However, real-world data of ocrelizumab in daily clinical practice remain scarce. The aim of this study was to evaluate the preliminary safety profile and effectiveness of ocrelizumab treatment for MS in an Arab population in a real-world clinical setting. Methods: In this retrospective single-center observational study in Qatar, we reviewed the medical records and analyzed the clinical and MRI data of all patients with relapsing-remitting MS (RRMS) and active secondary progressive MS (aSPMS)—between October 2017 through December 2020—who had received at least one infusion of ocrelizumab (Q-OCRE). Results: A total of 60 MS patients were included (57 with RRMS, three SPMS). The Median follow-up period was 19 months (range, 1–32). The most common reason for switching to ocrelizumab was increased disease activity and three-quarters of the patients were on a previous disease-modifying drug (DMD). No evidence of disease activity (NEDA) status at year 1 was achieved in 73% of the cohort. Mild infusion-related reactions (IRR) and infections were reported (mainly upper respiratory tract infections followed by urinary tract infection) with a declining percentage over the follow-up applications. No severe side effects were observed. Conclusion: Our real-world experience confirms good efficacy, tolerability, and safety of ocrelizumab in our Arab population.